Sistem Informasi Penyusunan Rencana Kerja Pemerintah (RKP) Desa Bidang Pembangunan Infrastruktur Berbasis Web: Studi Kasus : Desa Pandanlandung Kecamatan Wagir Kabupaten Malang - Yekti Asmoro Kanthi; Triyuni Triyuni Pratiwi; Sugeng Widodo (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2018)
Pandanlandung Village is one of twelve villages in the District of Wagir, Malang Regency which are given the authority to administer governance and development independently in accordance with UU No. 6 of 2014. Carrying out its authority, the village government needs to carry out the construction phase, one of which is planning that starts with village meetings and produces a draft RKPDesa. The preparation of RKPDesa is still done manually so that the process of documentation is long and there is no transparency in delivering the results of the deliberations to the community. One of the efforts to help compile the RKPDesa with an appropriate and efficient delivery process to the community requires an information system on the preparation of village government work plans. This study discusses the design of an information system for the preparation of the RKPDesa aimed at assisting the process of preparing village government work plans. The research methodology used is the method of analysis and design. The method of analysis consists of library studies, field surveys, and interviews, while the design method uses object oriented analysis and design. The results are expected to provide facilities to the village government in the form of applications to improve the performance of the village government so as to meet development goals and transparency to the community. The process of socializing to the village government will be carried out with a period of approximately 1 month